GNA14 Somatic Mutation Causes Congenital and Sporadic Vascular Tumors by MAPK Activation. - Lim, Young H; Bacchiocchi, Antonella; Qiu, Jingyao; Straub, Robert; Bruckner, Anna; Bercovitch, Lionel; Narayan, Deepak; McNiff, Jennifer; Ko, Christine; Robinson-Bostom, Leslie; Antaya, Richard; Halaban, Ruth; et al. (Am J Hum Genet, 2016)
Vascular tumors are among the most common neoplasms in infants and children; 5%-10% of newborns present with or develop lesions within the first 3 months of life. Most are benign infantile hemangiomas that typically regress by 5 years of age; other vascular tumors include congenital tufted angiomas (TAs), kaposiform hemangioendotheliomas (KHEs), and childhood lobular capillary hemangiomas (LCHs). Some of these lesions can become locally invasive and unresponsive to pharmacologic intervention, leading to significant complications. Recent investigation has revealed that activating mutations in HRAS, KRAS, NRAS, GNAQ, and GNA11 can cause certain types of rare childhood vascular tumors, and we have now identified causal recurrent somatic activating mutations in GNA14 by whole-exome and targeted sequencing. We found somatic activating GNA14 c.614A>T (p.Gln205Leu) mutations in one KHE, one TA, and one LCH and a GNA11 c.547C>T (p.Arg183Cys) mutation in two LCH lesions. We examined mutation pathobiology via expression of mutant GNA14 or GNA11 in primary human endothelial cells and melanocytes. GNA14 and GNA11 mutations induced changes in cellular morphology and rendered cells growth-factor independent by upregulating the MAPK pathway. Our findings identify GNA14 mutations as a cause of childhood vascular tumors, offer insight into mechanisms of oncogenic transformation by mutations affecting Gaq family members, and identify potential targets for therapeutic intervention.
Keywords: Cells, Cultured; Child, Preschool; Enzyme Activation; GTP-Binding Protein alpha Subunits; GTP-Binding Protein alpha Subunits, Gq-G11; Human Umbilical Vein Endothelial Cells; Humans; Infant; Infant, Newborn; Intercellular Signaling Peptides and Proteins; Male; MAP Kinase Signaling System; Melanocytes; Mitogen-Activated Protein Kinases; Mutation; Proto-Oncogene Proteins c-akt; Vascular Neoplasms

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms